Comprehensible Output: A Lesson from a Child Acquiring a First Language - Patuan Raja (TEFLIN, 2004)
The present article is intended to examine what a child acquiring a first language did when he encountered communication block in his interaction with others. More specifically, it examine linguistic output modification attempted by the child when he was not successful in getting his meaning across or in achieving his intended goal. The corpus data, in the form of cards containing naturally occurring utterances together with the context which were collected for one year, starting at age 1;6 and ended at 2;6 were part of a participant observation, parental-diary, naturalistic case study into his early language development. In his attempts to overcome a communication block, the child was found to make phonological, lexical, morphological, and syntactical elaboration, thus producing more comprehensible output. Relevant implications are then forwarded for the teaching of English in Indonesia.